If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + -15 + -1b = 1(b + 48) Combine like terms: -12 + -15 = -27 -27 + -1b = 1(b + 48) Reorder the terms: -27 + -1b = 1(48 + b) -27 + -1b = (48 * 1 + b * 1) -27 + -1b = (48 + 1b) Solving -27 + -1b = 48 + 1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -27 + -1b + -1b = 48 + 1b + -1b Combine like terms: -1b + -1b = -2b -27 + -2b = 48 + 1b + -1b Combine like terms: 1b + -1b = 0 -27 + -2b = 48 + 0 -27 + -2b = 48 Add '27' to each side of the equation. -27 + 27 + -2b = 48 + 27 Combine like terms: -27 + 27 = 0 0 + -2b = 48 + 27 -2b = 48 + 27 Combine like terms: 48 + 27 = 75 -2b = 75 Divide each side by '-2'. b = -37.5 Simplifying b = -37.5
| y=2.5x+4.25 | | 3(x-4)=66*11 | | ?d=5 | | 5z-z+3= | | 4x+159=2x+153 | | 35-17=3x-6 | | -8-12=20 | | 18+3x-x^2=0 | | 33x-9=90 | | (-2w)(2w-3)(3w+10)=0 | | 4x^2-33x+48=-4x+3 | | 3(5c-3)-2=13c+1 | | 4x(2x+y)= | | 6x+21=90 | | 4x+17=-17 | | 8x^2+2n-15=0 | | m(4-m)(5+m)=0 | | y=12.8x+24 | | 11b+7=50 | | 16-x=16x+10 | | -6+[x-4]=-6 | | -5(x+4)=50 | | (4u-3)(u+1)=0 | | 4x^5-12x^4=0 | | 12x+12=x+7 | | 3x-36-180=x | | 12+56=6(t+12) | | f(x^2)=5-2x | | -7-13v=32 | | 1.5x=10x | | 3(c+5)=18 | | 6x-(x+4)=4(x-2) |